3D‐printed surface‐modified aluminum nitride reinforced thermally conductive composites with enhanced thermal conductivity and mechanical strength. (29th December 2021) - Lee, Seonmin; Park, Dabin; Kim, Jooheon
Abstract: With the rapid miniaturization of electronic devices, novel thermally conductive composite materials are required for efficient thermal management. In this study, a straightforward strategy to fabricate thermally conductive composites, based on UV‐curable acrylate polymer using the DLP technique, was explored. Aluminum nitride (AlN), a ceramic filler with high thermal conductivity and mechanical strength, was functionalized with an acrylate bearing silane compound. This improved the interfacial adhesion between the filler and matrix, resulting in enhanced thermal conductivity. The thermal conductivity of the composite with 30 wt.% modified AlN was 0.42 W/mK, which is 3.5 times higher than that of neat UV‐cured acrylate resin (0.12 W/mK). The tensile strength also increased from 13.9 to 20.8 MPa before and after surface treatment due to improved filler‐matrix compatibility. The study demonstrates that 3D‐printing can be easily integrated into the fabrication of thermally conductive composites and filler surface modification can effectively enhance the thermal and mechanical strength of the composite.